An analysis of state-civil society relationships in Botswana : a case of the Women's Affairs Department and women non-governmental organisations - Mooketsane, Keneilwe (Department of Political Studies, 2015)
Interactions between the state and Non-governmental Organisations have been heightened globally. This has led to states engaging civil society more than ever before. However, tendencies to control NGOs by the state seem common in African countries. This dissertation seeks to examine relations between the state and NGOs in Botswana. Botswana is a democratic country, which has been hailed as stable and a strong state, however, civil society in Botswana remains weak. This creates a problem of a dominant state and weak civil society. The dissertation employs Najam's theoretical framework in trying to understand the extent of state dominance in the relationship between the state and NGOs in Botswana.